The Interaction of C60 on Si(111) 7 × 7 Studied by Supersonic Molecular Beams: Interplay between Precursor Kinetic Energy and Substrate Temperature in Surface Activated Processes - Aversa, Lucrezia; Taioli, Simone; Nardi, Marco Vittorio; Tatti, Roberta; Verucchi, Roberto; Iannotta, Salvatore (Frontiers in Materials, 2015)
Buckminsterfullerene (C60) is a molecule fully formed of carbon that can be used, owing to its electronic and mechanical properties, as “clean” precursor for the growth of carbon-based materials, ranging from -conjugated systems (graphenes) to synthesized species, e.g. carbides such as silicon carbide (SiC). To this goal, C60 cage rupture is the main physical process that triggers material growth. Cage breaking can be obtained either thermally by heating up the substrate to high temperatures (630°C), after C60 physisorption, or kinetically by using Supersonic Molecular Beam Epitaxy (SuMBE) techniques. In this work, aiming at demonstrating the growth of SiC thin films by C60 supersonic beams, we present the experimental investigation of C60 impacts on Si(111) 7x7 kept at 500°C for translational kinetic energies ranging from 18 to 30 eV. The attained kinetically activated synthesis of SiC submonolayer films is probed by in-situ surface electron spectroscopies (XPS and UPS). Furthermore, in these experimental conditions the C60-Si(111) 7×7 collision has been studied by computer simulations based on a tight-binding approximation to Density Functional Theory, DFT. Our theoretical and experimental findings point towards a kinetically driven growth of SiC on Si, where C60 precursor kinetic energy plays a crucial role, while temperature is relevant only after cage rupture to enhance Si and carbon reactivity. In particular, we observe a counterintuitive effect in which for low kinetic energy (below 22 eV), C60 bounces back without breaking more effectively at high temperature due to energy transfer from excited phonons. At higher kinetic energy (22 < K < 30 eV), for which cage rupture occurs, temperature enhances reactivity without playing a major role in the cage break. These results are in good agreement with ab-initio molecular dynamics simulations. SuMBE is thus a technique able to drive materials growth at low temperature regime.